Nonlinear Association between Physical Function and Risk of Mild Cognitive Impairment in Older Women with Low Muscle Mass - Ja-Gyeong Yang; Gwon-Min Kim; Seongryu Bae; Hyuntae Park (운동과학, 2022)
PURPOSE This study aimed to determine the nonlinear relationship between physical function and body composition in older women with mild cognitive impairment (MCI) and low muscle mass (LMM). Early prediction of sarcopenic MCI is important; however, it remains unclear whether improvements in physical function and cell health promote low rates of sarcopenic MCI in community settings. METHODS A total of 120 older women were enrolled, and subsequently stratified into the LMM group (n=90) and MCI with LMM group (n=30). MCI was evaluated by a clinician based on global cognitive function and clinical findings. RESULTS The results of hand grip strength (HGS), short-physical performance battery (SPPB), and 6-minute walk test (6 MWT) were found to be linearly associated with the risk of MCI. This result indicates that endurance capacity in the LMM with MCI group had an adjusted odds ratio of 3.69 (95% CI: 1.11–12.18). The nonlinearity of physical function on the risk of MCI was analyzed using the generalized additive models (GAM). CONCLUSIONS Physical function and body composition is significantly associated with LMM and MCI risk in aging adults. It is expected that the evaluation and improvement of kinematic indicators, such as HGS, SPPB, endurance, and PhA, could contribute to the prediction and prevention of MCI.